Analysis of Counseling Services and Mental Health Campaign Model Through Social Media - Khilman Rofi Azmi; Adilfi Riyanda Juang; Rizki Okta Rahmanda (Counselle| Journal of Islamic Guidance and Counseling, 2022)
Mental health is very influential in the welfare of life both physically and socially. People who are said to be mentally healthy are when they are free from various symptoms of mental illness. Symptoms of mental disorders include depression, fear, anxiety and so on. Mental health disorders can be prevented. Preventive action is by providing knowledge and awareness to the community, one of which is through social media. Mental Health Digital Platform Ibunda.Id campaigns for mental health using social media. This study aims to determine the technique of the Ibunda.Id digital platform in campaigning for mental health to the public through social media. The method used in this research is literature study and observation. This research uses a qualitative case study approach. The results of the discussion found that the ibunda.id Digital Platform in campaigning for mental health applied Collaborative Techniques with various parties and utilized social media including Instagram, Youtube, Facebook, and Websites. A verified Instagram account is one of the techniques for campaigning for mental health through social media using cool and unique content so that information can be easily conveyed clearly and accepted by the public. Mental health campaigned by the Ibunda.Id Digital Platform through social media is quite successful and has a good impact on the community